2019
DOI: 10.1002/adsu.201900020
|View full text |Cite
|
Sign up to set email alerts
|

The Structure–Activity Relationship in Membranes for Vanadium Redox Flow Batteries

Abstract: IntroductionWith the rapid increase of consumption of fossil fuels and the consequent environment pollution, there is an urgent need for the development and effective utilization of renewable energy sources like wind, solar, biomass, etc. However, these renewable energy sources are intermittent in nature, leading to the conflict between the seasonal and unstable electricity generation and requirement of the continuous and stable power supply for the end application. Thereby, energy storage Vanadium redox flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 232 publications
0
15
0
Order By: Relevance
“…In most studies on IEMs for VRFBs, selectivity is expressed as the ratio of ionic conductivity to vanadium permeability (i.e., κ/PV) 67 . Within the framework developed in the present study, the selectivity of CEMs used in VRFBs, αH/V, is obtained via: αH/V=CHmDHm4CVmDVm=κRT4F2PVCVs The factor of four in the denominator of Equation comes from the valence of VO 2+ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In most studies on IEMs for VRFBs, selectivity is expressed as the ratio of ionic conductivity to vanadium permeability (i.e., κ/PV) 67 . Within the framework developed in the present study, the selectivity of CEMs used in VRFBs, αH/V, is obtained via: αH/V=CHmDHm4CVmDVm=κRT4F2PVCVs The factor of four in the denominator of Equation comes from the valence of VO 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…In most studies on IEMs for VRFBs, selectivity is expressed as the ratio of ionic conductivity to vanadium permeability (i.e., κ=P V ). 67 Within the framework developed in the present study, the selectivity of CEMs used in VRFBs, α H=V , is obtained via:…”
Section: Permeability-selectivity Tradeoff In Iems For Vanadium Redox...mentioning
confidence: 99%
“…Nevertheless, it is worth mentioning that non‐perfluorinated membranes (AEM and CEM) and porous membranes with high ion selectivity and chemical stability are still the hotspots of the future development of ICRFB membrane materials [64] . Modifications of perfluorinated membranes, including inorganic‐organic hybrid, polymer blending, and amphoteric membranes need to be further investigated to ameliorate the ionic selectivity, as the developing trend of membranes for vanadium‐based RFB system [4,73] …”
Section: Research Status Of Key Components In Icrfbmentioning
confidence: 99%
“…On the other hand, it has been reported that the presence of hydrophilic particles like SiO 2 may also increase water uptake of the membrane, which enhances proton conductivity. [ 95 ] The FTIR‐ATR spectra of homogeneous perfluorosulfonic ionomer/silica composite membrane synthesized by Zeng et al. [ 96 ] showed a strong peak at 1105 cm –1 attributed to the Si–O–Si asymmetric stretching vibration, formed as a result of a condensation reaction between SiOEt/SiOH groups, but no peak at ≈940 cm –1 ascribed to Si–OH group.…”
Section: Polymer–particle Mixed Matrix Membranesmentioning
confidence: 99%